The infusion and acquisition of soft skills in real estate curriculum - Wilson Rangga Anthony Jiram, 1986-; Ahmad Ariffian Bujang; Fakulti Geoinformasi dan Harta Tanah (2013)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2013